--so they understand : cultural issues in oral history - Schneider, William S., 1946- (Utah State University Press, 2002)
Illuminated by numerous stories collected from Alaska, the Yukon, and South Africa and further enlivened by the author's accessible style and experiences as a longtime oral historian and archivist, So They Understand is a comprehensive study of the special challenges and concerns involved in documenting, representing, preserving, and interpreting oral narratives.